Preliminary results of olive mil wastewater treatment by immobilized microalgae - Martins, Bruna da Silva (2016)
The olive mill wastewater (OMW) is the principal industry residue extraction of olive oil. Generally is characterized by very high organic load, due to high levels of phenolic compounds and sugars, and have minimum levels of nitrogen compounds and low pH. A variety of biological processes and microorganisms have been tested to treat OMW, including bacteria, yeasts and fungi, where the effectiveness in reducing the toxicity varies greatly. Taking this into account, the aim of this work is to assess the potential of microalgae in the decrease of phenolic compounds in OMW. For this purpose, the effect of immobilized Chlorella vulgaris in OMW biotreatments has been tested in batch cultures. The effectiveness of the process has also been assessed by phytotoxicity, in germination trials of Lactuca sativa. Biotreatments have been performed with OMW dilutions of 35%, 50% and 60%. Results showed that C. vulgaris has the ability to remove phenolic compounds, achieving a final Phenolic Loss Index (PLI) of 73%. Regarding the phytotoxicity after biotreatment we can conclude that microalgae can reduce the toxicity of olive mill wastewaters also having the ability to degrade the phenolic compounds that inhibit the germination and growth of Lactuca sativa. Furthermore, the algae biomass obtained in this process could be valorized in other applications.